SEKSUALITAS MANUSIA SEBAGAI REALITAS DAN PANGGILAN KEPADA CINTA KASIH : Refleksi atas Hakekat Seksualitas Manusia - Moa, Antonius (UNIKA Santo Thomas, 2004)
Experience - both in practical and theoretical sphere - teaches and reminds us that sexuality is a reality inseperable from humanity. It is a human reality. Such a conviction rises a consequence of a deeper understanding that the whole being and existence of human being can only be understood, realized and lived within and through the reality of human sexuality itself, namely being male or female. None is neutral. As human being, he or she must be female or male. As such - being female or male - he/she is an image of God who are love. This implies that sexuality as a human reality is a call towards love.